Host resistances to Aphanomyces trifolii root rot of subterranean clover: first opportunity to successfully manage this severe pasture disease. (13th November 2015) - You, M. P.; O'Rourke, T. A.; Foster, K.; Snowball, R.; Barbetti, M. J.
Abstract : Subterranean clover ( Trifolium subterraneum ) is an important pasture legume in Australia (29 million ha) and elsewhere. However, severe pasture decline occurs in association with several root pathogens, including Aphanomyces trifolii, that has been misidentified for decades as A. euteiches until recently confirmed as A. trifolii . A series of controlled environment experiments was undertaken to identify host resistance to A. trifolii in subterranean clover and to compare virulence and phylogeny of isolates. In experiment 1, Dalkeith, Bacchus Marsh, Riverina and Yarloop were the most resistant of 38 cultivars with a percentage disease index (PDI) ≤10 for both tap and lateral roots. Experiment 2 confirmed resistance of Yarloop, but a change in some relative varietal resistances suggested physiological specialization among A. trifolii isolates. Experiment 3 confirmed extensive variation in virulence and physiological specialization across 23 isolates of A. trifolii, with three distinct clades, two of which were distinct from isolates collected previously. Experiment 4 identified host resistance(s) effective against a mixture of 20 A. trifolii isolates, but the most resistant cultivars (Antas, Uniwager, Leura) still showed significant disease. This is the first study to show physiological specialization in A. trifolii and to identify host resistance. This study defines A. trifolii as a significant but largely unknown contributor to severe root disease of subterranean clover in southern Australia. Finally, development and calibration of a new soil commercial DNA test not only enables field quantification of the disease, but development of appropriate breeding, selection and farm management strategies to reduce its impact.